Chronic Electrical Stimulation of the Intact Corticospinal System after Unilateral Injury Restores Skilled Locomotor Control and Promotes Spinal Axon Outgrowth - Carmel, Jason B. (Society for Neuroscience, 2010)
Injury to the brain or spinal cord usually preserves some corticospinal (CS) connections. These residual circuits sprout spontaneously and in response to activity-based treatments. We hypothesized that augmenting activity in spared CS circuits would restore the skilled motor control lost after injury and augment outgrowth of CS terminations in the spinal cord. After selective injury of one half of the CS tract (CST) in the rat, we applied 10 d of electrical stimulation to the forelimb area of motor cortex of the spared half and tested motor performance for 30 d. Rats with injury and CST stimulation showed substantial improvements in skilled paw placement while walking over a horizontal ladder. By the end of the testing period, the walking errors of the previously impaired forelimb in rats with injury and stimulation returned to baseline, while the errors remained elevated in rats with injury only. Whereas the time to perform the task returned to normal in all animals, the pattern of errors returned to normal only in the stimulated group. Electrical stimulation also caused robust outgrowth of CST axon terminations in the ipsilateral spinal cord, the side of impairment, compared with rats with injury only. The outgrowth was directed to the normal gray matter territory of ipsilateral CST axon terminations. Thus, stimulation of spared CS circuits induced substantial axon outgrowth to the largely denervated side of the spinal cord and restored normal motor control in the previously impaired limbs.